Period-Wise Phase Unwrapping Method With Two Gray Level Coding Patterns - Bolin Cai; Dongdong Xi; Lu Liu; Xiangcheng Chen; Yuwei Wang (IEEE Photonics Journal)
Fringe projection profilometry is a widely used three-dimensional (3D) optical measurement technique. However, it is quite challenging to quickly obtain the 3D information of objects. Minimizing the number of patterns for phase unwrapping is an efficient way to address the above problem, and many methods have been proposed. This paper reports a period-wise phase unwrapping method with only two gray level coding patterns. Due to a hybrid coding strategy implemented, the number of patterns used in the proposed method reduces by one in comparison with conventional gray level method when generating the same number of codewords. A robust decoding scheme is also developed to determine the fringe order, and its accuracy is guaranteed by using the self-correcting method to remove the phase errors. Some experiments have been conducted, and their results confirm that the success of the proposed method.